Evidence for developmental vascular-associated necroptosis and its contribution to venous-lymphatic endothelial differentiation - Meng, Han; Zhao, Youyi; Li, Yuqian; Fan, Hong; Yi, Xuyang; Meng, Xinyu; Wang, Pengfei; Fu, Fanfan; Wu, Shengxi; Wang, Yazhou (Frontiers in Cell and Developmental Biology, 2023)
During development, apoptosis removes redundant cells and ensures proper organ morphogenesis. Necrosis is long known as an adult-bound inflammatory and pathologic cell death. Whether there exists physiological necrosis during early development has been speculated but yet clearly demonstrated. Here, we report evidence of necroptosis, a type of programmed necrosis, specifically in perivascular cells of cerebral cortex and skin at the early stage of development. Phosphorylated Mixed Lineage Kinase Domain-Like protein (MLKL), a key molecule in executing necroptosis, co-expressed with blood endothelial marker CD31 and venous-lymphatic progenitor marker Sox18. Depletion of Mlkl did not affect the formation of blood vessel network but increased the differentiation of venous-lymphatic lineage cells in postnatal cerebral cortex and skin. Consistently, significant enhancement of cerebrospinal fluid diffusion and lymphatic drainage was found in brain and skin of Mlkl-deficient mice. Under hypobaric hypoxia induced cerebral edema and inflammation induced skin edema, Mlkl mutation significantly attenuated brain-blood-barrier damage and edema formation. Our data, for the first time, demonstrated the presence of physiological vascular-associated necroptosis and its potential involvement in the development of venous-lymphatic vessels.